2019
DOI: 10.1038/s41598-019-46088-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-212-3p inhibits the Proliferation and Invasion of Human Hepatocellular Carcinoma Cells by Suppressing CTGF expression

Abstract: MicroRNA-212-3p inhibits several human cancers but its effects on hepatocellular carcinoma (HCC) remain unclear. In this study, we show that miR-212-3p is down-regulated in HCC cell lines and tissues, and correlates with vascular invasion (p = 0.001), and the absence of capsule formation (p = 0.009). We found that miR-212-3p influenced the epithelial to mesenchymal transition (EMT) of HCCLM3 and Huh7 cells. Mechanistically, miR-212-3p repressed cell invasion through the suppression of connective tissue growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Moreover, we found that miR-195/497 cluster decreased the formation of regulatory transcription complex containing Yap and Smad3, while decreasing their common target genes, such as the gene-encoding CTGF ( Luo, 2017 ). Various studies have revealed that CTGF is critical in cancer progression and initiation ( Chen et al, 2019 ; Pu et al, 2019 ; Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that miR-195/497 cluster decreased the formation of regulatory transcription complex containing Yap and Smad3, while decreasing their common target genes, such as the gene-encoding CTGF ( Luo, 2017 ). Various studies have revealed that CTGF is critical in cancer progression and initiation ( Chen et al, 2019 ; Pu et al, 2019 ; Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects, if any, in HCC remained unclear. Thus, Chen et al (2019) examined the relationship between miRNA-212-3p and CCN2 in the hepatic TME. The authors showed that microRNA-212-3p inhibited proliferation of HCC cell lines through suppression of CCN2.…”
Section: Micro-rna Involvement In Hsc Activation In the Hepatic Tmementioning
confidence: 99%
“…For involvement of specific regulatory elements in the CCN2 gene we refer to Leask et al ( 2009 ). Furthermore, CCN2 expression can be regulated at the posttranscriptional and posttranslational level by various factors, including VEGF (Kondo et al 2006 ), hypoxia (Kondo et al 2002 ), tumor necrosis factor α (TNF-α), interferon gamma (IFN-γ) (Cooker et al 2007 ; Laug et al 2012 ), and a host of different microRNAs (miRNAs) (Cai et al 2018 ; Che et al 2019 ; Chen et al 2016 , 2019 ; Ernst et al 2010 ; Fox et al 2013 ; He et al 2017 ; Mu et al 2016 ; Qiao et al 2017 ; Sun et al 2016 ). For example, CCN2 and miRNA-21 are components of a positive feedback loop in pancreatic stellate cells, that may serve as an amplification mechanism for enhanced collagen production (Charrier et al 2014a ).…”
Section: Introductionmentioning
confidence: 99%